Factors associated with post-acute discharge location after hospital stay: a cross-sectional study from a Swiss hospital - Bettina M. Zimmermann; Insa Koné; Michael Rost; Agnes Leu; Tenzin Wangmo; Bernice S. Elger (BMC, 2019)
Abstract Background In 2012, Switzerland introduced the diagnosis-related group hospital payment system. Fearing that vulnerable patients may be discharged early, Acute and Transitional Care (ATC) was introduced to address the nursing care of patients who no longer needed an acute hospital stay. ATC is more costly for patients when compared to other discharge options like rehabilitation while providing less rehabilitative services. This study investigates factors associated with the place of discharge for patients in need of care. Methods Data was collected from 660 medical records of inpatients 50 years and older of the municipal hospital Triemli in Zurich, Switzerland. We used stepwise logistic regression to identify factors associated with their discharge into ATC or rehabilitation. Results Older patients with higher Delirium Observation Scale (DOS), lack of supplementary health insurance, resuscitation order and a lower social network were more likely to be discharged into ATC than rehabilitation. Conclusions The association of supplementary health insurance and social network with discharge into ATC or rehabilitation is problematic because patients that are already vulnerable from a financial and social perspective are potentially discharged into a more costly and less rehabilitative post-acute care facility.